Now that you want to take your HIV/AIDS vaccine/biological product research concept into the clinic: What are the "cGMP"?. Issue 15 (8th April 2015) - Sheets, Rebecca L.; Rangavajhula, Vijaya; Pullen, Jeffrey K.; Butler, Chris; Mehra, Vijay; Shapiro, Stuart; Pensiero, Michael
Abstract The Division of AIDS Vaccine Research Program funds the discovery and development of HIV/AIDS vaccine candidates. Basic researchers, having discovered a potential vaccine in the laboratory, next want to take that candidate into the clinic to test the concept in humans, to see if it translates. Many of them have heard of "cGMP" and know that they are supposed to make a "GMP product" to take into the clinic, but often they are not very familiar with what "cGMP" means and why these good practices are so important. As members of the Vaccine Translational Research Branch, we frequently get asked "can't we use the material we made in the lab in the clinic?" or "aren't Phase 1 studies exempt from cGMP?" Over the years, we have had many experiences where researchers or their selected contract manufacturing organizations have not applied an appropriate degree of compliance with cGMP suitable for the clinical phase of development. We share some of these experiences and the lessons learned, along with explaining the importance of cGMP, just what cGMP means, and what they can assure, in an effort to de-mystify this subject and facilitate the rapid and safe translational development of HIV vaccines.